2022
DOI: 10.1111/are.16143
|View full text |Cite
|
Sign up to set email alerts
|

Defatted black soldier fly larvae meal as a dietary ingredient for tambaqui ( Colossoma macropomum ): Digestibility, growth performance, haematological parameters, and carcass composition

Abstract: Black soldier fly (BSF, Hermetia illucens) meal is a prominent ingredient to keep up with the increasing demand of protein sources for aquafeeds. This study evaluated the digestibility of defatted BSF larvae meal (DBSFL) by indirect method, growth performance, haematological parameters, and carcass composition of tambaqui (Colossoma macropomum) fed diets containing DBSFL. The apparent digestibility coefficient of protein from DBSFL was 84.2%, corresponding to 42.9% of digestible protein. For the feeding trial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Most of these studies suggest protein alternatives by testing the impact of various sustainable feed formulations on performance. A wide variety of other aspects, such as digestibility, hematological markers, carcass composition (including fatty acid profile) and textural features, were investigated [37]. Research on the usage of insect meal or feeds based on processed waste from the aquaculture, pig and poultry industries are among the most present.…”
Section: Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies suggest protein alternatives by testing the impact of various sustainable feed formulations on performance. A wide variety of other aspects, such as digestibility, hematological markers, carcass composition (including fatty acid profile) and textural features, were investigated [37]. Research on the usage of insect meal or feeds based on processed waste from the aquaculture, pig and poultry industries are among the most present.…”
Section: Content Analysismentioning
confidence: 99%
“…By presenting an experimental trial on trout, Cappellozza et al [74] and Terova et al [75] recommended the utilization of insect meal. Trials have been also proposed for sea bass [76], tambaqui [37], zebrafish [77], sea urchins and other organisms [78]. Other studies advise using proteins from terrestrial animals and plants as a partial replacement.…”
Section: Content Analysismentioning
confidence: 99%
“…Our previous research has shown that tambaqui can be fed with full-fat BSFL to a replacement level of 50% of the commercial feed [15], and the full-fat or defatted BSFL can be added up to 15.75% [16] or up to 30%, respectively, in extruded feed without compromising tambaqui growth performance [17]. These studies were carried out with BSFL as a commercial feed substitute or as an ingredient in regular fish feed formulations, using ingredients such as soybean, corn, and wheat middlings.…”
Section: Introductionmentioning
confidence: 99%
“…The defatted BSFL meal (D-BSFL) is produced by partial or total fat extraction using pressing or organic solvents, and the resulting defatted meal is then posteriorly dried and ground. D-BSFL has around 60% protein and 10-12% lipid content [8,9]. The full-fat BSFL (FF-BSFL) meal is easy to produce by drying and posteriorly grinding.…”
Section: Introductionmentioning
confidence: 99%
“…Tambaqui easily adapts to feed formulations and aquaculture production systems [16]; in addition, it can be reared with the replacement of 50% commercial feed for whole BSFL without impairing its growth performance [19]. Furthermore, tambaqui digests 86% of the crude protein of the defatted BSFL meal, and levels of up to 30% defatted BSFL meal can be used in its fishmeal-free diet [9]. However, there are no published data on the use of full-fat BSFL meal in tambaqui diets.…”
Section: Introductionmentioning
confidence: 99%